UNIT 5A.9 Tetracycline‐Inducible and Reversible Stable Gene Expression in Human iPSC‐Derived Neural Progenitors and in the Postnatal Mouse Brain. (16th May 2017) - Akhtar, Aslam Abbasi; Breunig, Joshua J.
Abstract : The pB‐tet‐GOI plasmid system allows for stable piggyBac transposition‐mediated integration into cells, a fluorescent nuclear reporter to identify cells that have been transfected, and robust transgene activation or suppression upon the addition of dox to the cell culture or diet of the animal. Furthermore, the addition of luciferase downstream of the target gene allows for quantitative assessment of gene activity in a non‐invasive manner. The protocols herein provide instructions for the use of this system in cell lines and in the neonatal mouse brain. Specifically, a detailed protocol is provided to illustrate: (1) cloning of the respective GOI (genetic element(s) of interest); (2) nucleofection of the plasmid system into human induced pluripotent stem cell (iPSC)‐derived neural progenitors; (3) dox‐induced activation in vitro or in vivo; and (4) non‐invasive assessment of gene activity in vivo by bioluminescence imaging. © 2017 by John Wiley & Sons, Inc.